Teachers’ Perception on the Educational Values of the Traditional Games in South-western Nigerian Primary Schools - Victoria Oludunni Ogunniran; Surajudeen Adewale BADRU; Surajudeen Adewale BADRU (Universitas Pendidikan Indonesia (UPI), 2023)
This study investigated teachers’ perception on the educational values of the traditional games in South-western Nigerian primary schools. Studies had showed that traditional games had been relegated for the digital children’s games. Hence, the study was aimed to check the teachers’ views on the educational values and their supports for the games. Mixed approach was employed in collecting and analysing data. Questionnaire, interview and observation were methods of data collection. Purposive sampling techniques was utilised to sample ninety (90) teachers. Convenience sampling techniques was used to sample thirty (30) pupils for the observation exercise. The percentage was used to describe the demographic data of the participants, likewise, the question one was answered through the percentage. The research hypothesis 1 was tested using the T-test while the research hypothesis 2 was tested using Analysis of Variance (ANOVA) all at 0.05 level of significance. The qualitative data was analysed thematically. The result showed that there was no significant influence of the school type on teachers’ perception on the educational values of the traditional games. However, it was revealed that the class taught has significant influence on teachers’ perception on the educational values of the traditional games. Therefore, it was recommended that since the traditional games have educational values among pupils, the primary school educational stakeholders should therefore capitalise on these resources to develop educational skills: such as numeracy, communicative, leadership and health therapy in primary school pupils.